Development of Social Interaction and Behavior for Early Childhood Education in the Era Society (5.0) - Al Umairi, Mushab (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2023)
This research is based on the inability of young children to have good social interaction and behavior towards the environment, school, family, and society in the era of Society 5.0. To help reduce a child's inability to engage in social interaction and good social behavior. So, help from adults is needed. In providing this assistance, parents or teachers should understand the process of developing social interactions and social behavior for young children. This research aims to determine the development of social interaction and social behavior toward early childhood education in the era of Society 5.0. The type of research used in this research is field research. Then, to obtain data, this research used observation, interviews, and documentation methods. This research was analyzed using descriptive qualitative (in the form of opinions or written opinions from people and the actions observed). This research concludes that providing social interaction and good social behavior will positively impact early childhood education in the era of Society 5.0.